KURIKULUM PENDIDIKAN ISLAM BERBASIS TAUHID ASMA WA SIFAT - Rini Fitria (Edukasi Islami: Jurnal Pendidikan Islam, 2014)
Asma wa Shifat Tauheed is one of three fundament of Tauheed. Unfortunately, this condition has not get appreciation and attention seriously for Islamic people. Especially, Asma wa Shifat from implications perspective is very important for a Moslem life. Asma wa Shifat can give solution for multi dimension crisis in Indonesian Islamic Education.There are many ways and methods can do by academicians and practitioners Islamic education for elimination crisis multi dimension in Islamic education. The ways and methods are by repair materials of curriculum Islamic education in Indonesian. The fundament materials of curriculum are Asma wa Shifat Tauheed in Ahlus Sunnah wal Jama’ah perspective which can give to repair student personality and student character. The curriculum used by theory and practice as structured and systemic to bear out put Iman, taqwa and good personality are dream and expectation will be reality.